PEMANFAATAN OBJEK FAVORIT UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERPEN PADA SISWA KELAS XI SMA NEGERI 1 KALASAN - Danu Denri Susilo; Aris Daryono; Denik Wirawati (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
This study aims to find out whether the use of favorite objects can improve students' short story writing skills and to identify effective teaching strategies in using favorite objects as inspiration in writing short stories. The research method used in this study was Classroom Action Research (PTK) which lasted for 2 cycles. The subjects of this study were students of class IX MIPA 2, academic year 2022/2023, which consisted of 36 students. The research instrument used was an observation sheet (observation). Technical data analysis of this research uses descriptive qualitative and quantitative analysis. Based on the results of research on the pre-cycle, cycle 1, and cycle 2, it was found that there was an increase in short story writing skills starting from the pre-cycle, cycle 1, and cycle 2, namely 68.88; 80; and 88.88. In addition, based on the results obtained in this study, it is known that the implementation of using favorite objects has an effect on improving the short story writing skills of class XI MIPA 2 students.